Evaluation of the effectiveness of “Shega” natural and self-made solution as compared to permethrin lotion in eliminating head lice in infested Schoolchildren in Gondar area, Ethiopia: a randomized non-inferiority trial - Tessema, Tewodros Ayalew; Cavin, Anne-Laure; Gurmu, Abyot Endale; Limenh, Liknaw Workie; Bizuneh, Gizachew Kassahun; Adamu, Betelhem Anteneh; Befekadu, Annisa; Dagne, Henok; Graz, Bertrand (Frontiers in Pediatrics, 2025)
BackgroundHead lice infestation among schoolchildren leads to social stigmatization, psychological distress, superinfection, and lack of concentration because of sleeplessness. Head lice infestation is universal and not found solely in privileged populations. Although there are modern medicines for the treatment of head lice, most communities are unable to access them due to high prices, limited supply in remote areas, or lack of willingness to use them because of the negative attitudes towards head lice infestation amongst children and the community. Therefore, this study assessed the effectiveness of a homemade remedy (“Shega solution”) made with easily available ingredients at a low cost as compared to the standard Permethrin 1% lotion.MethodThe study was conducted in the Amhara region of Ethiopia in five schools in Gondar city and the surrounding district. The selected school children were randomly assigned to intervention (Shega) and control (Permethrin) groups. The study was designed as a non-inferiority trial, with the hypothesis that Shega would, at worst, be only marginally inferior to standard treatment, by a margin (=delta) not exceeding 30 percentage points. A theatre play was created and performed in front of the whole school community to familiarize the school children with the study and to remove stigmatization about head lice infestation.ResultsThree hundred and eighty-four schoolchildren were included in the study. About 67.7% of participants were cured in the intervention group compared to 83.3% in the control group. The difference of 15.6 points of percentage is within the set acceptable range, with a 95% CI difference in the proportion of success of 7.2–24.1 for the difference in success rates. The theatrical event was noted as useful in breaking the social stigma and familiarizing the children with the research project.ConclusionThe study has shown that the homemade remedy, Shega solution, has the potential to treat a fair proportion of head lice infestations as compared to the standard treatment, permethrin. The theatre performed in front of the school children has the potential to help the implementation of such projects at community levels. This study also indicates the level of effectiveness of permethrin lotion in Ethiopia for the first time. Clinical Trial Registrationhttps://pactr.samrc.ac.za/Search.aspx, identifier (PACTR202208887378021).